Physical fitness evaluation-interpretation software - Ortega, F.; Ruiz, J.; Rodriguez, G.; Gutierrez, A.; Castillo M. (International Journal of Computer Science in Sport, 2002)
To have a high physical fitness is a health index, while to present low physical fitness is a cardiovascular disease risk factor and a mortality predictor. Therefore, it seems necessary to dispose of simple and reliable procedures to evaluate not only the health status but the disease risk level according to physical fitness markers. In addition, before an exercise training program is prescribed it is necessary to know the patient`s physical fitness level. We have designed and validated simple and automatic software to assess and interpret the physical fitness level. Our software allows easy and fast data interpretation, and provides different comparisons between subject`s physical fitness level and reference values from the scientific literature (1,2,3,4,5). The software design is based on the use of a data-base and a spreadsheet. Once the results are obtained and the comparisons automatically showed, the disease risk is predicted but only for those diseases with enough scientific evidence available. The software is able to show a report about a self-reported physical activity questionnaire. The software allows registering a high number of people through automatic alphanumeric variables codification.